Memory as a foundation for approach and avoidance decisions: A fertile area for research. - Sklenar, Allison M.; Leshikar, Eric D. (Memory & Cognition, 2025)
Scant research has directly measured the extent episodic memory serves as the basis for decisions, particularly decisions to approach or avoid other people (i.e., social targets). In this theoretical paper, we survey the limited work showing the relationship between episodic memory and subsequent approach or avoidance decisions about social targets, including descriptions of significant limitations of past work. We then describe three important areas for future work in this domain (explicit memory, implicit memory, diagnosticity) as a framework to generate new foundational knowledge about the extent memory influences approach and avoidance decisions. Overall, the framework proposed in this work should lead to better understanding of the connection between memory and decision-making, especially decisions to approach or avoid social targets (i.e., other people).